DIFFUSE ST DEPRESSION WITH ST ELEVATION AVR IN ACUTE CORONARY SYNDROME AND ITS ASSOCIATION WITH SIGNIFICANT LEFT MAIN OR THREE VESSEL CORONARY ARTERY DISEASE AND ITS CONFOUNDERS - Ahmed, Salman; Khatti, Shehzad; Shah, Ghazanfar Ali; Khan, Naveedullah; Rai, Lajpat; Khan, Mohammad Zeb; Bari, Syed Abdul; Roy, Naveen (Journal of Ayub Medical College Abbottabad, 2023)
Background: Global ST depression in 8 or more leads along with ST elevation in aVR has been considered as hallmark of widespread sub-endocardial ischemia. It has been associated with left main (LM) stem or three vessel disease (3VD). But different studies have shown different results. We collected data from patients to see association of these ECG changes with significant LM stem disease and/or significant (3VD). Methods: It was a prospective observational study performed at tertiary care cardiac center. All patients with acute coronary syndrome (ACS) having global ST depression and ST Elevation in aVR (that is ST depression of at least 0.5 mv in ‰¥8 leads along with ST elevation in aVR of at least 0.5 mv) and have undergone coronary angiogram were included. Results: Our study included 404 patients with above mentioned ECG findings. We observed significant LM stem or significant 3VD in 67% (n=274), 3VD in 55% (n=222) and significant LM stem in only 29% (n=118). Risk factors like diabetes, hypertension and smoking increase probability of these ECG changes up to 40.4%, 32.1% and 33.3% for significant LM stem disease and 62.7%, 57.1% and 57.5% for significant 3VD. Magnitude of ST elevation in aVR leads ‰¥1 mm increase sensitivity for LM stem disease 35% and for 3VD up to 60.4% and TIMI score ‰¥4 up to 36.7% for significant LM stem disease and 62.5% for significant 3VD. Conclusion: Global ST depression along with ST elevation in aVR in patients with ACS has low probability for significant LM stem intermediate probability for significant 3VD. Factors like presence of diabetes, hypertension, smoking, magnitude of ST elevation in aVR, and TIMI score improves its diagnostic yield.